Cynara cardunculus L. as a Multipurpose Crop for Plant Secondary Metabolites Production in Marginal Stressed Lands - Pappalardo, Helena Domenica; Toscano, Valeria; Puglia, Giuseppe Diego; Genovese, Claudia; Raccuia, Salvatore Antonino (Frontiers in Plant Science, 2020)
Cardoon (Cynara cardunculus L.) is a Mediterranean crop, member of the Asteraceae family, characterized by high production of biomass and secondary metabolites and by a good adaptation to climate change, usable in green chemistry, nutraceutical, and pharmaceutical sectors. Recent studies demonstrated the ability of cardoon to grow up in a stressful environment, which is associated with enhanced biosynthesis of biologically active compounds in these plants, and this effect is increased by abiotic stresses (salt, heat, pollution, and drought stress) that characterize many world marginal areas, affected by the climate changes. The plant response to these stresses consists in implementing different processes that modify some plant biological functions, such as alleviating both cellular hyperosmolarity and ion disequilibrium or synthesizing antioxidant molecules. The aim of this work was to investigate different cardoon response mechanisms to abiotic stresses and to evaluate their influence on the biologically active compounds biosynthesis. Following this purpose, we analyzed the ability of cardoon seeds to germinate under different salt stress conditions, and on the sprouts obtained, we measured the total phenol content and the antioxidant activity. Moreover, the growth of cardoon seedlings grown under heavy metals stress conditions was monitored, and the expression levels of heavy metal transport–associated genes were analyzed. The results showed the ability of cardoon plants to tolerate abiotic stress, thanks to different defense mechanisms and the possibility to obtain biomass with high content of biologically active molecules by exploiting the natural tolerance of this species for abiotic stresses. Moreover, we identified some important genes encoding for metal transportation that may be involved in arsenic and cadmium uptake and translocation in C. cardunculus. Then, this species can be considered as a promising crop for green chemistry and energy in marginal lands.